Biodegradation Efficacy of Bacillus cereus and Pseudomonas aeruginosa on Polythene Bags - F. A., Sabiya; F. M, Ahmed; K. A., Abubakar; P., Vandi (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
Plastic pollution arises as the second obvious threat to the world environment after global warming. This is a descriptive cross-sectional research design aim to evaluate the efficiency of bacteria as biodegradable organisms on polythene bags. The selected bacterial isolate was identified by morphological characterization like shape, size, structure, texture, appearance, elevation and colors. Phenotypic characteristics such as microscopic characterization of gram reaction, motility were performed the standard protocols. Bacillus cereus degrades 1.000g of polythene bag in 30 days to 0. 975g. Pseudomonas aeruginosa degrades 1.000g of polythene bag in 30 days to 0. 955g. The percentage of polythene bags loss at day 30 was 3.10% weight loss when treated with Bacillus cereus, when treated with Pseudomonas aeruginosa at day 30, the percentage lost was 4.50%. The overall investigation can be concluded that P. aeruginosa and other species exhibited significant polythene degradation ability and in the near future, Pseudomonas sp. can be used to reduce the quantity of plastic waste, which is rapidly accumulating in the natural environment. Among the two isolates tested.